The Demand for Labour: A Post Keynesian Appraisal - Túñez Area, Narciso (Iberian Journal of the History of Economic Thought, 2015)
This paper is concerned with ambiguities in the Post Keynesian model regarding the nature of the functions involved in the determination of the demand for labour. Those ambiguities have led to misleading representations of Keynes’s theories regarding the demand for labour and to conceptually travesties effective demand schedules. These controversial concepts will be analysed in reference to Keynes’ original reflections. Furthermore, this paper offers a different analysis from those of Allain (2009), Hartwig (2011), Hayes(2013), Lavoie (1992) and Chick (1983), but also from the Weintraub (1956) and Davidson’s (1994) Z and AD theoretical framework.